PENGARUH CITRA ARTIS TERHADAP MINAT MENONTON FILM DILAN 1991 BAGI REMAJA (KASUS CITRA IQBAAL RAMADHAN DI AKUN INSTAGRAM FANPAGE @DILANKU) - Muflihunna Syam; Evawani Elysa Lubis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The artist's image is a picture of the self made by the artist regarding the appearance of himself and the accompanying feeling based on the assessment of the views of others towards him. The presence of the 1991 Dilan movie that was able to attract more than five million viewers and formed a fanpage Instagram account, namely @dilanku. This account is an Instagram official account from fans of the film Dilan which contains Dilan movie footage and Dilan film promotions. The @dilanku account shows a lot of positive comments from Dilan movie viewers who identified the figure of Iqbaal with Dilan so as to produce an image for the artist Iqbaal. The theory used in this study is the Stimulus-Response theory. The purpose of this study was to determine the magnitude of the effect of the artist's image on the interest in watching Dilan 1991 movie in adolescents on my @dilanku fanpage Instagram account.This study uses quantitative research methods, with data collection techniques, namely through distributing questionnaires using Google Form online to followers of Instagram accounts @dilanku with a total sample of 207 which were determined through purposive sampling technique. Data analysis techniques in this study using explanatory statistical techniques.The results of this study indicate that the level of influence of the image on watching Dilan 1991 films on @dilanku followers has a big effect. This is seen from the simple regression in this study is Y = 11,748 + 0,291X + e. the constants value is 11,748 and the artist image variable coefficient is 0,291. Meanwhile based on the results of the hypothesis test it is known that the significance value of 0,000 is smaller than α = 0.05. Based on the Model Summary table shows that the value of R = 0.473, and the coefficient of determination (R square) is 0.223 in moderate correlation. This figure shows the understanding that the influence of the artist's image on interest in watching is 22.3%. While the remaining 77.7% is influenced by other variables not included in this study.